if the sum of two expressions is 3x+5 and one expression is 5x-7 what is the other expression

Question

if the sum of two expressions is 3x+5 and one expression is 5x-7 what is the other expression

in progress 0
Thiên Thanh 3 months 2021-08-28T08:18:24+00:00 1 Answers 2 views 0

Answers ( )

    0
    2021-08-28T08:20:19+00:00

    Answer:

    -2x + 12

    Step-by-step explanation:

    If we call our other expression y, we can set up an equation tying together 3x + 5, y, and 5x – 7:

    (5x-7)+y=3x+5

    Solving for y by subtracting 5x – 7 from both sides will get us the expression we’re looking for:

    y=3x+5-(5x-7)\\y=3x+5-5x+7\\y=-2x+12

    So the other expression in the sum is -2x + 12.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )